Interacting Effects of Eyespot Number and Ultraviolet Reflectivity on Predation Risk in Bicyclus anynana (Lepidoptera: Nymphalidae). Issue 6 (12th December 2019) - Chan, Ian Z W; Rafi, Fathima Zohara; Monteiro, Antónia
Abstract: Small marginal eyespots on lepidopteran wings are conspicuous elements that attract a predator's attention to deflect attacks away from the body, but the role of ultraviolet (UV) reflectivity at the center of these patterns and variation in eyespot number in altering the function of eyespots remains unclear. Here, we performed a field-based predation experiment with artificial prey items based on the appearance of squinting bush brown butterflies Bicyclus anynana (Butler, 1879). We tested how two visual properties of the wing pattern affect predation risk: i) the number of eyespots on the ventral forewing surface—two or four; and ii) the UV reflectivity of eyespot centers—normal (where the UV reflectivity of the centers contrasts strongly with that of the darker surrounding ring) or blocked (where this contrast is reduced). In total, 807 prey items were deployed at two sites. We found a significant interaction between the number of ventral forewing eyespots and UV reflectivity in the eyespot centers: in items with fewer eyespots, blocking UV resulted in increased predation risk whereas in items with more eyespots, blocking UV resulted in decreased predation risk. If higher predation of paper models can be equated with higher levels of wing margin/eyespot conspicuity, these results demonstrate that UV reflectivity is an important factor in making eyespots more conspicuous to predators and suggest that the fitness of particular butterfly eyespot number variants may depend on the presence or absence of UV in their centers and on the ability of local predator guilds to detect UV.